Analisis Penggunaan E-Commerce: Faktor Yang Mempengaruhi dan Dampaknya Bagi UMKM - Muhammad Wildan Affan (Jurnal Akademi Akuntansi, 2022)
The Internet of Things (IoT), which is marked by the development of e-commerce, has changed business models, especially MSMEs. However, the development of e-commerce cannot be widely accepted by MSME actors. Therefore, this study aims to analyze the factors that influence the use of e-commerce and its impact. The sample was determined by using a non-probability sampling technique based on convenience sampling. Research respondents are MSME actors who use e-commerce. The results show that trust and interactivity have an influence on the use of e-commerce by MSMEs and an increase in the use of e-commerce will improve MSME performance. Therefore, MSME actors will use e-commerce to improve their performance, however, will consider e-commerce that can be trusted and has good interaction facilities between sellers and buyers.